2017
DOI: 10.1037/gdn0000075
|View full text |Cite
|
Sign up to set email alerts
|

Perceived self-to-other similarity as a mediator of the effects of gender and racial composition on identification in small groups.

Abstract: for his help and support during my work on this project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition, people quickly determine which subgroup they belong to in order to simplify their social world (Hoog and Terry, 2000). Researchers (Garcia, 2017;Johnson and Avolio, 2018) confirm that employees identify with coworkers based on perceived similarity to one another. As such, we predict that visible dissimilarity may stimulate individuals to self-segregate into minority subgroups.…”
Section: Group Identificationmentioning
confidence: 97%
“…In addition, people quickly determine which subgroup they belong to in order to simplify their social world (Hoog and Terry, 2000). Researchers (Garcia, 2017;Johnson and Avolio, 2018) confirm that employees identify with coworkers based on perceived similarity to one another. As such, we predict that visible dissimilarity may stimulate individuals to self-segregate into minority subgroups.…”
Section: Group Identificationmentioning
confidence: 97%
“…Fortunately, the burgeoning awareness of the importance of identity statuses to individuals' behaviors in, and capacity to derive benefit from, group psychotherapy is giving rise to research on linkages between members' perceptions of one another's identities and group behavior. For example, Garcia (2017) found that when members see one another as sharing an identity status, they are poised to recognize similarities between them. Conversely, when they believe they are in a different racial or gender identity category, they are primed to see differences between them.…”
Section: Implications For Conducting Groupsmentioning
confidence: 99%